Identification of Ancylostoma Duodenale Eggs in Pregnant women with Anemia at Kusuma Bangsa Community Health Center, Pekalongan City - Ghofur, Abdul; Nisa Kamilya, Miladia (INDOGENIUS, 2025)
Background & Objective: Helminthiasis is a public health problem that can affect nutritional status and cause anemia, especially in vulnerable groups such as pregnant women. One type of worm that plays a role in anemia is Ancylostoma duodenale, which lives in the small intestine and can cause chronic blood loss. This study aimed to identify Ancylostoma duodenale eggs in pregnant women with anemia at Kusuma Bangsa Health Center, Pekalongan City. Method: This study used a descriptive design with a sample of 11 pregnant women with anemia at the Kusuma Bangsa Community Health Center, Pekalongan City. Ancylostoma duodenale eggs were examined using sedimentation method. Result: The examination results showed that all samples were negative for Ancylostoma duodenale worm infection. Factors supporting the negative results were that most respondents had implemented good personal hygiene, such as the habit of washing hands with running water, using footwear when leaving the house, always cutting nails at least once a week, and washing raw vegetables before consumption, so as to prevent transmission of helminthiasis. Conclusion: In conclusion, there was no Ancylostoma duodenale infection among pregnant women with anemia at Kusuma Bangsa Community Health Center, Pekalongan City.